Identification of Lack of Fusion and Penetration in Circumferential Fillet Weld by Phased Array Ultrasonic Method in Gas Industry - Konar, Radoslav; Mician, Milos; Mesko, Jozef; Sventek, Michal (Communications - Scientific letters of the University of Zilina, 2015)
The article deals with non-destructive ultrasonic identification of lack of fusion and penetration in circumferential fillet welds in gas industry by using Phased Array method. These types of welds are used mainly for repairs of gas pipelines during operation. The main aim of this paper is to compare results of measurements of the weld with and without defect. Phased Array testing procedures for circumferential fillet welds methods are also described in this article.